2015
DOI: 10.1007/s11430-015-5125-3
|View full text |Cite
|
Sign up to set email alerts
|

A 2680-year record of sea ice extent in the Ross Sea and the associated atmospheric circulation derived from the DT401 East Antarctic ice core

Abstract: Long time series of Antarctic sea ice extent (SIE) are important for climate research and model forecasting. A historic ice extent in the Ross Sea in early austral winter was rebuilt through sea salt ions in the DT401 ice core in interior East Antarctica. El Niño-Southern Oscillation (ENSO) had a significant influence on the sea salt deposition in DT401 through its influence on the Ross Sea SIE and the transport of sea salt inland. Spectral analysis also supported the influence of ENSO with a significant 2-6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Barry and Dayton (1988) speculated that changes in zonal winds associated with the 1982-83 ENSO event might have been responsible for the strong northerly flows in McMurdo Sound during the 1980s. Li et al (2015) found connections between ENSOs and PDOs in the ice records and suggested the existence of teleconnections from the PDO to McMurdo Sound. There was a large PDO in the late 1990s that correlates nicely with our observations.…”
Section: Icebergblockingmentioning
confidence: 88%
“…Barry and Dayton (1988) speculated that changes in zonal winds associated with the 1982-83 ENSO event might have been responsible for the strong northerly flows in McMurdo Sound during the 1980s. Li et al (2015) found connections between ENSOs and PDOs in the ice records and suggested the existence of teleconnections from the PDO to McMurdo Sound. There was a large PDO in the late 1990s that correlates nicely with our observations.…”
Section: Icebergblockingmentioning
confidence: 88%
“…-77.37 39.70 3810 607 1904 (Motizuki et al, 2017; (Traufetter et al, 2004) DML15C98_14 (FB9814) -75.08 2.50 2970 1766 1996 (Sommer et al, 2000) DML17C98_33 (B33) -75.17 6.50 3160 0 1996 (Sommer et al, 2000) DSS0506 -66.77 112.81 1370 1927 1989 (Vallelonga et al, 2016) DT401 -79.02 77.00 3760 0 1998 (Ren et al, 2010a;Li et al, 2015;Li et al, 2012;Yang et al, 2019; (Bertler et al, 2004;Bertler et al, 2011;Bertler et al, 2005) Vostok5G (Bertler et al, 2004) Table S2. List of sites in the CLIVASH2k chemistry database which have been identified as having a statistically significant correlation with sea ice concentration (SIC), winds (v850 and u850) or geopotential height (z500).…”
Section: Df01mentioning
confidence: 99%